The Variability of Inflation - Foster, Edward (The Review of Economics and Statistics, 1978)
TWO separate policy issues have led to discussion of a preferred rate of inflation: the possible choice between inflation and jobs, and the choice between taxes on money balances and taxes of other kinds. Okun (1971) for the first of these issues and Logue and Willett (1976) for the second, among others, have remarked that the discussion is typically conducted as though a more inflationary policy means a rise from one steady rate to a higher steady rate. The world might not be like that; a rise in the average rate of inflation might mean, inevitably, a rise in its variability. Okun presented some to suggest that countries with higher rates of inflation do experience more variable rates and suggested why it might be so; Gordon (1971) called the evidence into question. Logue and Willett presented further results that supported Okun's position; but their results did not support Okun in the case of highly industrialized countriesthe ones that concerned him. Below I summarize these findings and report additional that supports Okun for highly industrialized as well as other countries. The reason for Okun's concern is that variability of inflation imposes costs on the economy that we should consider when we choose a macroeconomic policy.' Section II supports the claim that there is an empirical relation across countries between the average rate of inflation and the variability of that rate; but it says nothing about the slope, or even the existence, of a functional relation between them that represents an opportunity locus for a single country. In section III, I conclude with a brief discussion of this issue.